Income Aspiration, Income Comparison and Life Satisfaction: The case of Turkish Migrants in the Netherlands - DUMLUDAĞ, DEVRİM (SPRINGER, 2022)
This study examines the effects of income aspiration and social and economic comparison (with a wide range of reference groups) on the life satisfaction of Turkish immigrants in the Netherlands by using a new and a more direct approach. This is made possible with a unique data set applied to a representative sample of 1006 respondents that includes individual data on reported satisfaction with life, as well as a sufficient income evaluation measure as a proxy for individuals' aspiration levels. The proxy measure for social and economic comparison is the evaluation of socioeconomic status on the ladder. Respondents not only assess their socio-economic position on the ladder, but also evaluate the reference groups' position as well. The results reveal that life satisfaction of respondents' is negatively correlated with their income aspiration level, controlling for the effect of income and other socio-demographic and socio-economic variables. The estimates for the dummy specifications reveal that the perception of a worse living standard than Dutch natives is significantly and negatively correlated with the life satisfaction of Turkish immigrants. Furthermore, the high coefficient for comparison with people in Turkey indicates that the reference groups in the country of origin do not lose their importance and effect. For life domain reference groups, both upward and downward evaluations are statistically significant.
Keywords: Happiness; Life satisfaction; Relative income; Income aspiration; Socioeconomic status; Social comparison; Immigrants; RELATIVE-INCOME; SOCIAL-STATUS; SET-POINT; HAPPINESS; IMMIGRANTS; ADAPTATION; COLLECTIVISM; MIGRATION; PATTERNS; EUROPE